Enhancement of Gain in L-Band Bismuth-Based Erbium-Doped Fibre Amplifier Using an Un-pumped EDF and Midway Isolator - Chong, Wu Yi; Harun, Sulaiman Wadi; Ahmad, Harith (Institute of Physics, 2004)
A hybrid L-band erbium-doped fibre amplifier (EDFA) with enhanced gain characteristic is demonstrated without a significant noise figure penalty. It uses a backward C-band amplified stimulated emission from both the ends of a bismuth-based EDFA system to pump an unpumped erbium-doped fibre (EDF) for gain enhancing. The maximum gain enhancement of 4.0dB is obtained at wavelength 1604nm with EDF length of 20m. The gain spectrum is reasonably flat in this amplifier compared with the amplifier without an EDF. The gain varies from 27.4dB to 30.2dB at wavelength region 1564-1608nm with incorporation of 20m EDF. Noise figure also varies from 6.0 to 7.7dB at this wavelength region.